2021
DOI: 10.3390/ijms222011108
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Inflammasome Inhibitor BAY-117082 Reduces Oral Squamous Cell Carcinoma Progression

Abstract: Oral cancer is one of the most common human malignancies, and its incidence is increasing worldwide. In particular, oral squamous cell carcinoma (OSCC) is characterized by high rates of proliferation, invasiveness, and metastasis. Currently, standard treatment for OSCC includes surgical removal, chemotherapy, and radiotherapy; however, the survival rate of patients with OSCC remains low, thus new therapies are needed. It has been proven that excessive NLRP3 inflammasome activation and apoptosis alteration may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 49 publications
(94 reference statements)
1
9
0
Order By: Relevance
“…The involvement of inflammasome in bladder cancer [13], gastric cancer [14], and leukemia [15] has been highlighted by several studies; however, the role of NLRP3 in DM due to OSCC has not been fully elucidated. Scientific evidence has shown that BAY 11-7082, a powerful inhibitor of the NLRP3 inflammasome [16], possesses various pharmacological abilities; it is also able to modulate the apoptosis process [17]. The purpose of this study was to evaluate the effect of BAY-117082, a selective NLRP3 inflammasome inhibitor, in an in vivo orthotopic model of OSCC and its role in the invasiveness and metastasis processes in neighbor organs such as lymph nodes, lung, and spleen tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of inflammasome in bladder cancer [13], gastric cancer [14], and leukemia [15] has been highlighted by several studies; however, the role of NLRP3 in DM due to OSCC has not been fully elucidated. Scientific evidence has shown that BAY 11-7082, a powerful inhibitor of the NLRP3 inflammasome [16], possesses various pharmacological abilities; it is also able to modulate the apoptosis process [17]. The purpose of this study was to evaluate the effect of BAY-117082, a selective NLRP3 inflammasome inhibitor, in an in vivo orthotopic model of OSCC and its role in the invasiveness and metastasis processes in neighbor organs such as lymph nodes, lung, and spleen tissues.…”
Section: Introductionmentioning
confidence: 99%
“…It can also inhibit NLRP3 inflammasome independently of NF-κB [376]. Its efficacy has been demonstrated in several animal models [377][378][379][380]. Due to its small molecular weight (207.25 Da), this molecule can easily cross the BBB [381], making it attractive for alleviating CNS symptoms of MPS.…”
Section: Reagents Capable Of Inhibiting Nlrp3 Inflammasomementioning
confidence: 99%
“…In addition, BAY also suppresses the translocation and activation of AP-1, interferon regulatory factor-3 (IRF-3), and signal transducer and activator of transcription-1 (STAT-1) by inhibiting the phosphorylation or activation of ERK, p38, and JAK-2 ( 192 ). BAY is also an inhibitor of NLRP3 inflammasome and a modulator of apoptosis pathways shown in the management of psoriasis-like dermatitis and oral cancer ( 193 , 194 ). These suggest that BAY could serve as a lead compound in developing potent anti-inflammatory drugs with multiple targets in inflammatory responses.…”
Section: Pharmacological Targeting Of Nf-κb and Er Stress In Atherosc...mentioning
confidence: 99%